2020
DOI: 10.1108/ijrdm-09-2019-0321
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage EBM-based approach to evaluate operational performance of unattended convenience store

Abstract: PurposeDue to recent technological advances, the retail industry has changed significantly. This paper examines a novel unmanned retail mode-unattended convenience store to identify the possible operational problems and develop appropriate managerial recommendations.Design/methodology/approachA data-driven two-stage epsilon-based measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Many of the marketing differences identified across the target markets were related to the vending distribution mix, specifically the different types of locations (POS and external) and Marketing of vending channels cross-selling of packaged drinks. Similarly, Yao et al (2020) concluded that locations and surrounding environments are essential for improving the business performance of unmanned convenience stores. The industry experts interviewed in our pre-study also noted that three of the elements of the distribution mix are related to the locational factor, suggesting that location is the most important distribution characteristic in vending channels.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the marketing differences identified across the target markets were related to the vending distribution mix, specifically the different types of locations (POS and external) and Marketing of vending channels cross-selling of packaged drinks. Similarly, Yao et al (2020) concluded that locations and surrounding environments are essential for improving the business performance of unmanned convenience stores. The industry experts interviewed in our pre-study also noted that three of the elements of the distribution mix are related to the locational factor, suggesting that location is the most important distribution characteristic in vending channels.…”
Section: Discussionmentioning
confidence: 99%
“…Although it does not focus on the proportion of output and input changes (non-radial technique), the Slack-Based Measure (SBM) must deal with slacks directly. SBM simulations (non-radial slack variable efficiency), are based on the efficiency of slack variables but do not use the radial estimate assumption, and aim to optimize output and input inefficiencies by picking locations farthest from the border [16,[35][36][37]. They lack data on the ratio used to compute the efficiency front projection during the technique.…”
Section: The Ebm Theorymentioning
confidence: 99%
“…To solve this issue, Tone offered three Epsilon-Based Measurement (EBM) models with "radial and non-radial components" in 2010 [16]. Among the designs were "input-oriented, output-oriented, and non-oriented" and "non-oriented" [16,25,37]. The models considered both non-radial and radial features.…”
Section: The Ebm Theorymentioning
confidence: 99%
“…Finally, with the increasing importance of unattended retail which-along with vending machines-includes unattended convenience stores and supermarkets at the test stage (Yao et al, 2020), future scholars can adopt a cross-channel perspective in measuring marketing synergy while integrating spillover effects (e.g. Kim and Lee, 2020).…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 99%